Examining Social Media Marketing and Destination Image Effects on Satisfaction and Revisit Intention with City Branding Moderation - Rifka Yusdia Sasmita; Andriani Kusumawati; Swasta Priambada (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Tourism drives economic growth, cultural preservation, and regional income, yet the iconic Floating Market in Banjarmasin City has seen visitor numbers drop sharply from 79,120 in 2023 to 61,356 in 2024. Modern land infrastructure, river pollution, and limited facilities have diminished its traditional charm, prompting the need for smarter promotion strategies. This study investigates how social media marketing and destination image affect tourist satisfaction and revisit intention, with city branding acting as a moderator, among visitors to Banjarmasin’s Floating Market. Data were gathered via an online questionnaire from 250 tourists and analyzed using PLS-SEM in SmartPLS version 4. The results show that social media marketing and destination image both positively influence tourist satisfaction. Destination image and tourist satisfaction significantly affect revisit intention, while social media marketing has no direct effect on revisit intention. Most importantly, city branding moderates the relationship between social media marketing and revisit intention, strengthening the path when city branding is high. These findings highlight the urgent need for Banjarmasin authorities and market managers to weave a consistent “City of a Thousand Rivers” brand into social media campaigns. Combining authentic cultural storytelling with improved site conditions can revive visitor interest, enhance satisfaction, and secure long-term loyalty for this unique heritage attraction.